The Fermentum in the Historical Context of the Roman Liturgy - Celiński, Łukasz (Verbum vitae, 2025)
This contribution is a historical study of the ancient Roman practice of fermentum, which was already established and attested in the city of Rome at the beginning of the 5th century. Despite the scarcity of documentation relating to this liturgical practice, a critical study of the sources, together with their broader context, offers a more complete view of the phenomenon. Our study offers a critical re-evaluation not only of the liturgical sources themselves, but also of the opinions of leading scholars of the past regarding the Roman practice of fermentum.